2019
DOI: 10.3390/membranes9010010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Mixed-Gas Permeability, Sorption and Diffusion of CO2-CH4 Mixtures in 6FDA-mPDA Polyimide Membrane: Unveiling the Effect of Competitive Sorption on Permeability Selectivity

Abstract: The nonideal behavior of polymeric membranes during separation of gas mixtures can be quantified via the solution-diffusion theory from experimental mixed-gas solubility and permeability coefficients. In this study, CO2-CH4 mixtures were sorbed at 35 °C in 4,4′-(hexafluoroisopropylidene)diphthalic dianhydride (6FDA)-m-phenylenediamine (mPDA)—a polyimide of remarkable performance. The existence of a linear trend for all data of mixed-gas CO2 versus CH4 solubility coefficients—regardless of mixture concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 45 publications
(106 reference statements)
10
66
0
Order By: Relevance
“…3a and S6. This modeling approach has demonstrated good agreement with experimental mixed-gas sorption for PIM-1, TZ-PIM, PTMSP, 6FDA-HAB and its TR450 analog, 6FDA-mPDA, CTA, and PMMA 20,22,24,25,30,52,76 . Thermodynamically rigorous models such as the nonequilibrium lattice fluid (NELF) 77 model would provide more robust mixed-gas predictions 24,78 , but lattice fluid parameters (i.e., , ) cannot be directly determined for * * , * the PIMs studied in this work because the polymers degrade below their glass transition temperature 79,80 .…”
Section: Pure-gas Sorption Tests and Mixed-gas Sorption Predictionsmentioning
confidence: 59%
“…3a and S6. This modeling approach has demonstrated good agreement with experimental mixed-gas sorption for PIM-1, TZ-PIM, PTMSP, 6FDA-HAB and its TR450 analog, 6FDA-mPDA, CTA, and PMMA 20,22,24,25,30,52,76 . Thermodynamically rigorous models such as the nonequilibrium lattice fluid (NELF) 77 model would provide more robust mixed-gas predictions 24,78 , but lattice fluid parameters (i.e., , ) cannot be directly determined for * * , * the PIMs studied in this work because the polymers degrade below their glass transition temperature 79,80 .…”
Section: Pure-gas Sorption Tests and Mixed-gas Sorption Predictionsmentioning
confidence: 59%
“…38 When we tested these PIM-PI polymers using a 50:50 molar CO 2 -CH 4 mixture, the permeability vs. partial pressure behavior was preserved; in addition, we found that for both polymers over the entire pressure range, CO 2 and CH 4 mixed-gas permeabilities were lower than the corresponding pure-gas values ( Figure selectivity is predominant and lowers the CO 2 /CH 4 mixed-gas permeability selectivity of a polymer membrane material relative to its respective pure-gas value. [41][42][43] However, some polymers that can better resist CO 2 -induced plasticization demonstrated CO 2 /CH 4 mixture permselectivity matching or even slightly outperforming their respective pure-gas values. 16,25 This is also the case for 6FDA-TrMCA and 6FDA-TrMPD, (Figure 10), some hydroxyl-functionalized polyimides and their thermally rearranged derivatives such as 6FDA-HAB 44 and TDA1-APAF 45 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, it is important to consider the polymer matrix plasticization capability of CO 2 in mixed-gas environment. In fact, the presence of CO 2 locally dilates the glassy polymer matrix, thereby enhances the methane diffusion coefficient leading to faster CH 4 diffusion in mixed-gas conditions than obtained in pure-gas tests [41][42][43]. Thus, CO 2 -induced plasticization depresses the diffusion selectivity of glassy polymers; this counteracts with the fact that solubility selectivities of CO 2 -CH 4 mixtures are higher than those obtained under ideal pure-gas conditions -as demonstrated and quantified in several examples [41][42][43].…”
mentioning
confidence: 99%
“…Contrarily to the just described permeation behavior of CO 2 in the mixture, CH 4 mixed-gas permeability of both 6FBBA-TMDAT and CA increased with partial pressure. Experimental studies on CO 2 –CH 4 pure- and mixed-gas permeability, sorption and diffusion in glassy polyimide and rubbery polydimethylsiloxane membranes [ 66 , 67 ] showed that this CH 4 permeability enhancement is directly correlated to CO 2 sorption; i.e., increasing CO 2 content in the polymer matrix activates chain mobility thus boosting CH 4 diffusion coefficient. Hence, the occurrence of this phenomenon explains the decrease in CO 2 /CH 4 permselectivity under mixed-gas conditions in both 6FBBA-TMDAT and CA ( Figure 11 c).…”
Section: Resultsmentioning
confidence: 99%